HUBUNGAN INTENSITAS CAHAYA DENGAN KEJADIAN ASTENOPIA PADA DEWASA AWAL - Naldi Feriansyah; Revalita Wahab (Fakultas Kedokteran Universitas Trisakti, 2025)
Asthenopia, also known as visual fatigue, is a group of symptoms caused by excessive use of the eyes. One of the aetiologies of asthenopia is light intensity. Lighting of minimal intensity can cause discomfort around the eyes, as well as tired and strained eyes. On the other hand, too much light can cause glare. It is therefore important to ensure that lighting is sufficient and appropriate. This will affect the effectiveness of the work. The aim of this study was to investigate the relationship between light intensity and asthenopia. The study was a cross-sectional study with an observational-analytical design. Data collection using questionnaires and light measurements using lux meters was conducted on 39 samples obtained through consecutive sampling at Bank X, West Jakarta in November 2023. Data analysis was performed using the Fisher test with a significance level of p<0.05. The prevalence of asthenopia in Bank X was 79.48%. Poor light intensity of 61% based on 39 points of the respondents' workbenches. More male respondents (57%) experienced asthenopia. And permanent employment status more (69%) have asthenopia. Analysis using the Fisher test showed no association between accommodation insufficiency and asthenopia (p = 0.003).There is a significant association between light intensity and asthenopia in early adulthood.